Osvežitev spomina na znamenite Slovence v Gradcu - Karničar, Ludvik (Slavia Centralis, 2020)
The author of the article emphasizes the importance of refreshing the memory of famous Slovenes in Graz, e.g. Janez Nepomuk Primic, Gregor Krek and Karel Štrekelj.
Keywords: important personalities; Slovenes; Austria; Graz